Lowered intraocular pressure in a glaucoma patient after intravitreal injection of ocriplasmin - McClintock M (Dove Medical Press, 2015)
Michael McClintock,1 Mathew W MacCumber1,2 1Department of Ophthalmology, Rush University Medical Center, 2Illinois Retina Associates, S.C., Chicago, IL, USA Abstract: We report the case of a glaucoma patient who received a single intravitreal injection of 125 µg ocriplasmin for vitreomacular traction in the right eye. The patient had bilateral advanced glaucoma and had previously undergone an implantation of an Ahmed glaucoma valve in the right eye and trabeculectomy in both eyes. The patient was using three topical ophthalmic intraocular pressure (IOP)-lowering medications on the day of injection. Baseline uncorrected Snellen visual acuity was 20/80-1 and IOP was 19 mmHg. Resolution of vitreomacular traction was achieved 1 week after injection. IOP was transiently decreased, reaching a maximum reduction of 12 mmHg below baseline at 1 month after injection, when serous choroidal effusion was also present. IOP returned to baseline levels and choroidal effusion resolved at 2 months after injection of IOP-lowering medication. Vitrectomy with epiretinal membrane and internal limiting membrane peeling, endolaser photocoagulation, and fluid–gas exchange were performed in the right eye ~3.5 months after injection to treat persistent epiretinal membrane, and presumed tractional retinal detachment. Final visual acuity was 20/50+ and IOP was 18 mmHg at 16 weeks after surgery. To our knowledge, this is the first report of IOP reduction and serous choroidal effusion after ocriplasmin injection. Keywords: ocriplasmin, intraocular pressure, vitrectomy, choroidal effusion